ANALISIS KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS KECAMATAN KONGBENG KABUPATEN KUTAI TIMUR - Marjoni Rachman Abdul Muis (ADMINISTRASI PUBLIK, 2017)
Quality Analysis of Health Services at the Community Health Center Kongbeng District East Kutai Regency, under the guidance of Dr. Marjoni Rachman, M.Si as Supervisor I and Suhardiman, S.Sos, M.Si as Supervisor II.This study aims to find and describe the Quality of Health Services in the Community Health Center of Kongbeng Sub-district of East Kutai Regency. The approach used in this research is qualitative descriptive approach. In this research will be description of five indicators, namely Tangibles, Reliability, Responsiveness, Assurance and Emphaty.The results showed that the Quality of Health Service in Puskesmas Kecamatan Kongbeng East Kutai Regency got a score of 66.15% and this included in the category is quite good. Thus the formulation of problems and hypotheses in this study have been answered and proven well.